College of Sciences
Department of Mathematical Sciences
EXAM 1 SOLUTION
Complex Analysis I
MATH 315 SECTION 01 CRN 23516
9:30 10:45 on Monday & Wednesday
Due Date: Monday, October 19, 2009
Complex Analysis I
EXAM 1 SOLUTION
Fall, 2009
wz =1+i 3
3+i =1 3+i
31
[(
]
(
)(
)
)2
2
zw =
3+i
1+i 3 = 3+i 3+i
3 + 1 = 3 3 + i ( 3 + 1 ) = 4i
( ) 2
3 + 12 = 3 + 1 = 2
z = 3 + i =
)(
)
(
3i
1+i 3
w
1+i 3
1+i 3
3i
3+i
2 3 + 2i
=
=
=
=
.
=
( )2
z
4
2
3+i
3+i
3i
3 +1
z =  z  ei Arg(z) = 2ei 6 .
where n is an integer.
3. (Total 5 points) Determine whether the following is true (T) or false (F).
(3.1) (3 points) If Im(z) > 0, then  z i  >  z + i . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . F
Answer. z = i satises the condition Im(z) = 1 > 0. But, clearly z = i does not satisfy the
inequality
z i = 0 < 2 = z + i.
(3.2) (2 points) If z = 0 lies inside the unit circle centered at the origin, then 1/
z lies outside the
circle. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . T
Answer. With z = x + iy = 0,
1
1
x + iy
=
= 2
,
z x iy
x + y2
and
1
= 1
.
z
x2 + y 2
Page 1 of 5
Complex Analysis I
EXAM 1 SOLUTION
Fall, 2009
1
Arg ( z ) = tan
= tan1 1 = ,
1
4
(
1
Arg ( w ) = tan
1
1
)
= tan1 ( 1 ) =
Since w = z, so zw = z z =  z 2 = 2 and
z
z
z2
z2
2i
= =
=
= i,
2 =
w
z zz
2
z
Arg ( zw ) = Arg ( 2 ) = 0,
Arg
(z )
= Arg ( i ) = .
w
2
The arguments, arg ( z ), arg ( w ), arg ( zw ), arg ( z/w ), are obtained adding 2n, integer n, to
the principal arguments.
y
,
x
and
Arg(z) (, ].
and
Arg(
z ) (, ].
)12
6. (5 points) Express 1 + i 3
Answer. Since z = 1 + i 3 has the modulus  z  = 2 and the principal argument Arg ( z ) = ,
3
so it has the exponential form,
[
(
)
(
)]
+ 2k + i sin
+ 2k
1 + i 3 = 2ei( 3 +2k ) = 2 cos
3
3
where k = 0, 1, 2, . . . . By de Moivres formula, we deduce
(
)
(
) ] }12
(
)12 { [
1+i 3
+ 2k + i sin
+ 2k
= 2 cos
[
(3
) 3
(
)]
12
12
12
=2
cos
+ 12 2k + i sin
+ 12 2k
3
3
= 212 [ cos ( 2n ) + i sin ( 2n ) ] = 212 = 4096 + i0,
where k, n = 0, 1, 2, . . . .
Page 2 of 5
Complex Analysis I
EXAM 1 SOLUTION
Fall, 2009
z 3 =  z 3 ei3 arg( z ) ,
1 + i =  1 + i  ei arg( 1+i ) =
2ei( 4 +2n )
2ei( 4 +2n ) ,
 z 3 =
i.e.,
2,
3 arg ( z ) =
+ 2n.
4
It gives us
( )1/3
2
= 21/6 ,
z =
arg ( z ) =
2n
+
,
12
3
i.e.,
z = 21/6 ei( 12 +
2n
3
i
1
+
3
c2 = c1 = 21/6 ei( 12 3 ) =
2 2
)
)
(
(
1/6
1
+
2
3
i
1
c0 = 21/6 e ( 12 ) =
2 2
1/6
2
2 i
c1 = 21/6 ei( 12 + 3 ) =
.
2
),
z + z
,
2
y = Im ( z ) =
z z
.
2i
Before putting them into the function, we modify the given function
f (z) = xy + iy 2 = y ( x + iy ) = ( Im ( z ) ) z,
which gives us
z z
z 2 z z
z 2  z 2
 z 2 z 2
f (z) = ( Im ( z ) ) z =
z = i
= i
=
i.
2i
2
2
2
Page 3 of 5
Complex Analysis I
EXAM 1 SOLUTION
Fall, 2009
(8.2) (5 points) Write f (z) = z 2 z2 in the form u(r, ) + iv(r, ), where r and are the modulus
and the principal argument of z, respectively.
Answer. With z = rei and z = rei , we have
)
(
f (z) = z 2 z2 = r2 e2i r2 e2i = r2 e2i e2i
= r2 [ cos ( 2 ) + i sin ( 2 ) ( cos ( 2 ) i sin ( 2 ) ) ]
= 0 + 2r2 i sin ( 2 ) = u(r, ) + iv(r, ).
9. (5 points) Sketch and nd the image S of the semiinnite strip S given below under the transformation w = f (z) = ez :
S = { z = (x, y) C  1 x 1, 0 y } .
Answer. Using Exponential Form. For z = x + iy S, we use the exponential form,
ei = w = f (z) = ex+iy = ex eiy ,
i.e.,
= ex ,
= y.
0 v(x, y) = ex sin y e.
That is, for z S, the real and imaginary parts of f (z) = u + iv, Re(f (z)) = u(x, y) = ex cos y and
Im(f (z)) = v(x, y) = ex sin y, should be in the intervals, e u e and 0 v e, respectively.
Finally we observe that for z S,
(
)
u2 + v 2 = ( ex cos y )2 + ( ex sin y )2 = e2x cos2 y + sin2 y = e2x ,
e2 u2 + v 2 e2 ,
Complex Analysis I
EXAM 1 SOLUTION
Fall, 2009
Region S'=fHSL
Region S
0
1
2
1
0

 1 0
lim
z 1+i
z 2 + z2
Answer.
(
lim
z 1+i
)
2
z 2 + z2 = ( 1 + i )2 + ( 1 + i ) = (1 + i)2 + (1 i)2 = 2i 2i = 0.
(
(10.2) (5 points) lim
zi
xe
xy
exy
i
x+1
lim
(x,y) (0,1)
xexy i
exy
= 0 i = i.
(x,y) (0,1) x + 1
lim
11. (5 points) Find the set of all points at which the given function is continuous.
{
f (z) =
Im(z)
,
z
0,
z=
0
z = 0.
Answer. We recall that a continuous function and Re ( z ) and Im ( z ) are continuous everywhere.
Im(z)
It implies
is continuous except z = 0, i.e., f (z) is continuous everywhere except z = 0. So
z
we look for the continuity of f (z) at z = 0.
Case 1. Horizontal Approach: z = (x, y) (0, 0) along the xaxis, z = (x, 0) (0, 0),
Im(z)
0
=
lim
=
lim 0 = 0.
(x,0) (0,0)
(x,0) (0,0) x + i0
(x,0) (0,0)
z
lim
Case 2. Vertical Approach: z = (x, y) (0, 0) along the yaxis, z = (0, y) (0, 0),
Im(z)
y
1
1
=
lim
=
lim
= = i.
(0,y) (0,0)
(0,y) (0,0) 0 + iy
(0,y) (0,0) i
z
i
lim
Since two limits are dierent, so the limit does not exist at z = 0 and f (z) is not continuous at
z = 0. Therefore, f (z) is continuous everywhere except z = 0.
Page 5 of 5
EXAM 2 { SOLUTION
Complex Analysis I
ID No:
Solution
Name:
Solution
Score:
50/50
Complex Analysis I
EXAM 2 { SOLUTION
Fall, 2009
1. (5 points) Show that f 0 (z ) does not exist at any point for f (z ) = ez.
Proof.
With z = x + iy ,
2. (5 points) Show that the function f (z ) = e cos (ln r) + ie sin (ln r) is dierentiable in the
domain of denition r > 0, 0 < < 2 , and also to nd f 0 (z ).
Proof.
Let u(r; ) = e cos (ln r) and v (r; ) = e sin (ln r). Then we observe
1
1
ur =
e sin (ln r) =
v;
u = e cos (ln r) =
r
r
1
1
vr = e cos (ln r) = u;
v = e sin (ln r) =
r
u;
v
At any z = rei in the given domain, u and v satisfy the Cauchy{Riemann equations, i.e.,
rur = v = v ;
u = u = rvr :
Thus, f (z ) is dierentiable in the given domain and has the derivative
1
1
f 0 (z ) = e i (ur + ivr ) = e i
v+i u
r
= ir
i
(u + iv ) = iz
Remark:
We observe
f (z ) = e cos (ln r) + ie sin (ln r) = e ei ln r = ei(ln r+i) = ei log z = z i ;
where log z is a branch of the logarithm. So when we dierentiate it, we get f 0 (z ) = iz 1 i . In
fact, the answer above implies
f 0 (z ) = iz 1 e [cos (ln r) + i sin (ln r)] = iz 1 f (z ) = iz 1 z i = iz 1 i :
x3 + 3xy 2
Proof.
vx
vy dy
@
2y
@x
6xy;
ux dy
Z
3x2 + 3y 2
6xy + 0 (x) =
0 (x) = 0;
(x) = C:
Therefore, we deduce the harmonic conjugate v (x; y ) = 2y
constant.
Page 1 of 4
dy
= 2y
3x2 y + y 3 + (x);
uy ;
3x2 y + y 3 + C , where
is any
Complex Analysis I
EXAM 2 { SOLUTION
Fall, 2009
4. (5 points) Find the harmonic conjugate v (x; y ) of the harmonic function u(x; y ) = 2x (1
such that f (z ) = u(x; y ) + iv (x; y ) satises f (0) = 1.
Answer.
v
vy dy
2x =
uy
ux dy
@
@x
= vx =
= 2 (1
2y
y ) dy
y 2 + (x)
=2
vx ,
1 2
y + (x) = 2y
2
= 0 (x);
y)
i.e.,
y 2 + (x);
(x) = x2 + C:
We deduce
v (x; y ) = 2y
y 2 + x2 + C;
f (z ) = u(x; y ) + iv (x; y ) = 2x (1
y 2 + x2
i,
2y
y 2 + x2 + C :
and thus,
f (z ) = 2x (1
i;
y) + i
y) + i
2y
y 2 + x2
i :
Answer.
p
p
1 + i 3 = j1 + i 3jei arg(1+i 3) = 2ei( 3 +2n) ;
p
n = 0;
1; 2; : : :
and
= 2ei( 3 +2n) ;
ex
Thus, we conclude
z
Proof.
= ln 2 + i
= 2;
x = ln 2;
i:e:;
+ 2n
n = 0;
+ 2n:
1; 2; : : : :
ejzj .
2
With z = x + iy , we have
z2
= x2
y 2 + 2xyi;
jz j2 = x2 + y2; ej j = e
e = ex y ex +y = ejz j ;
z2
i:e:;
ez
x2
= ex
x2 +y 2
2 y 2 2xyi
z2
= ex
2 y2
Page 2 of 4
Complex Analysis I
7. (5 points) Evaluate log
Answer.
p
log
EXAM 2 { SOLUTION
3+i .
By the denition,
3 + i = ln 3 + i + i arg
3 + i = ln 2 + i
Answer.
have
Fall, 2009
z2
+ 2n
i
n = 0;
1; 2; : : : :
Because the principal value Log z is one of the values of the logarithm log z , so we
eLog z
= z;
6= 0:
It implies
z
Log z 2 i
i=e
) = e 2 i = cos
+ i sin
= i;
z2
= 2i:
+ 2n;
i:e:;
= z 2 = 2i = 2ei( 2 +2n) ;
r2
Therefore, we deduce
z
= 2ei( 4 +n) ;
i:e:;
z1
= 2;
i:e:;
= 2ei 4 = 1+ i;
Page 3 of 4
= 2;
and
2 =
z2
= 2ei( 4 +) =
+ n:
(1 + i) :
Complex Analysis I
EXAM 2 { SOLUTION
Fall, 2009
P: V:
Answer.
e
Log
because
< Arg
P: V :
e
e
i
e
3i
= ln
e
3i
2
3
< .
By the denition,
)) = e3i(1
3=2
3i
, i.e.,
)) :
1 i 3
2
i=1
3
2
i;
3
Thus, we deduce
2 i
3
1 i 3
1+i 3
2
= ln e
3
Proof.
3 +i
3i
e
= e3i Log( 2 (
= e3i Log( 2 (
By the denition,
P: V :
e
= e(3=2) log(
1+i 3
p
3=2
e2 :
= 2 2.
):
1+i 3
p
p
p
2
1 + i 3 = ln 1 + i 3 + i arg 1 + i 3 = ln 2 + i
+ 2n ;
3
p 3
3
2
3
3
log 1 + i 3 = ln 2 + i
+ 2n = ln 2 + i ( + 3n ) = ln 2 + i (3n + 1) ;
2
2
3
2
2
p
p
3 ln 2+i(3n+1)
3 ln 2 i(3n+1)
(3=2) log( 1+i 3)
3
=
2
= e2 e
= 2 (1) = 2 2:
e
= e2
log
Page 4 of 4